2022
DOI: 10.1111/1475-6773.14112
|View full text |Cite
|
Sign up to set email alerts
|

Racial and ethnic disparities in excess mortality among U.S. veterans during the COVID‐19 pandemic

Abstract: Objective The COVID‐19 pandemic disproportionately affected racial and ethnic minorities among the general population in the United States; however, little is known regarding its impact on U.S. military Veterans. In this study, our objectives were to identify the extent to which Veterans experienced increased all‐cause mortality during the COVID‐19 pandemic, stratified by race and ethnicity. Data Sources Administrative data from the Veterans Health Administration's Corp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Sustained higher outpatient use may be due to patients with PCC, which merits exploration in future work and has potential implications for VA workforce planning. Third, subgroup analyses found that the short-term visit increase following COVID-19 infection was greater for older veterans, veterans with a high comorbidity burden, Hispanic veterans, rural veterans, and veterans who were not vaccinated . Improved access to telehealth for these more vulnerable veterans may benefit them and their caregivers, if telehealth obviates the need for caregivers to provide veterans with travel for care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sustained higher outpatient use may be due to patients with PCC, which merits exploration in future work and has potential implications for VA workforce planning. Third, subgroup analyses found that the short-term visit increase following COVID-19 infection was greater for older veterans, veterans with a high comorbidity burden, Hispanic veterans, rural veterans, and veterans who were not vaccinated . Improved access to telehealth for these more vulnerable veterans may benefit them and their caregivers, if telehealth obviates the need for caregivers to provide veterans with travel for care.…”
Section: Discussionmentioning
confidence: 99%
“…Veteran characteristics were chosen for subgroup analyses according to differences reported in the clinical severity of COVID-19 infection, 26 , 27 , 28 including age groups (20-44, 45-54, 55-64, 65-74, 75-84, and ≥85 years), sex, self-reported race, self-reported Hispanic ethnicity, smoking status, immunosuppression at index date, vaccination status at index date, rural or urban residence, comorbidity burden (defined as Gagne score 29 quartiles), and the pandemic wave in which the infection occurred. 30 Race and ethnicity in the VA Corporate Data Warehouse are collected through self-identification either at enrollment or at a health care encounter and are included in this study for descriptive purposes and because outpatient visits are known to vary by race and ethnicity.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, while this analysis focused on institutional characteristics of facilities, future work should identify the extent to which facility-level variation in excess mortality is driven by differences in the characteristics of the veterans in their catchment areas (eg, by urban/rural, race/ethnicity). For instance, Feyman et al found that White veterans experienced a lower rate of excess mortality during the pandemic compared with veterans of color 25…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Feyman et al found that White veterans experienced a lower rate of excess mortality during the pandemic compared with veterans of color. 25 Our study results could be used to identify the highest and lowest-performing facilities and investigate what influenced their performance. Specifically, the VHA could send mixed-methods researchers to these facilities and conduct surveys and qualitative interviews with management and clinical staff to learn more about what happened.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding education, one study indicated that all-cause mortality rates were approximately 2 times higher among adults with the least education than among those with the most [ 31 ]. Another study indicated that veterans’ mortality rates varied substantially by racial and ethnic group [ 32 ]. However, the “other Hispanic” and “higher than high school” populations had the highest risks of all-cause mortality associated with multimorbidity.…”
Section: Discussionmentioning
confidence: 99%